Implementasi Extreme Programming pada Aplikasi "SIATAP" Sistem Informasi Tanya Apoteker Berbasis Android dan Website - Rizki Wahyudi; Agus Junadi; Haryani; Andi Saryoko; Donna Setiawati; S.M Santi Winarsih; Gustin Setyaningsih (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2020)
The pharmacist is a professional degree for someone who has taken the oath of pharmacist position. Pharmacists are expected to be able to improve knowledge, skills, behaviour to be able to interact with patients. The form of interaction is giving information on medicines and counselling. In its service, pharmacists identify, prevent, overcome drug-related problems, and this has the possibility of medication errors. This research aims to build communication media between pharmacists and patients "SIATAP". The application will be developed using the extreme programming method. The advantages of this method can increase client satisfaction due to good communication so that it gets direct input from clients. Android application is designed for communication media between pharmacists and patients, the website application design to manage data for the administrator and pharmacist. To ensure the feasibility of the system, testing is done by using alpha and acceptance testing. The results of the alpha testing of all functional systems can run as expected. The results of the Acceptance Testing, using a questionnaire obtained a percentage of 92.57% with the conclusion that the application can be a good response from users so that the application is feasible to be implemented. The application can be downloaded at the URL: http://bit.ly/2ATy6hT.